Barr-Zee diagrams at a high-energy muon collider - Samuel Homiller; Jackie Lodman; Aditya Parikh; Matthew Reece (Journal of High Energy Physics)
Abstract The sensitivity of electron EDM experiments has been increasing at a rapid pace, and could yield indications of new physics in the coming decade. An intriguing possibility is that an EDM signal could be generated by new, electroweak-charged particles at the TeV scale that couple to the Higgs and contribute to the electron EDM at two-loop order via Barr-Zee diagrams. A high-energy muon collider could decisively search for new physics at this scale. In this work, we explore this complementarity between colliders and EDM experiments, and note that Barr-Zee diagrams from the aforementioned particles are closely related to vector-boson scattering processes at a muon collider. These loop corrections lead to kinematic features in the differential cross sections of these processes, dictated by the optical theorem. We demonstrate this connection in the context of the singlet-doublet and doublet-triplet extensions to the SM, explore the detectability of these features at a muon collider experiment, and discuss how these measurements can be used to ascertain the underlying model parameters.